Market Entry Strategies in Eastern Europe in the Context of the European Union An Empirical Research into German Firms Entering the Polish Market - Klug, Michael (Deutscher Universitätsverlag : Imprint: Deutscher Universitätsverlag, 2006)
The preparations for market entry in a foreign country include various aspects and are influenced by factors inside and outside the firm. Based on face to face interviews with decision makers of 16 German firms Michael Klug analyses the applied strategy and the motivation for market entry and investigates different strategy theories like Porter's market based view for their suitability to explain the firms' strategy abroad. The author discusses the operational design including forms of market presence and marketing mix to realise a chosen strategy and shows the influence of the European Union as an institutional arrangement for firms preparing a venture abroad.